Help them grow or watch them go : career conversations organizations need and employees want - Kaye, Beverly, 1943-; Giulioni, Julie Winkle (Berrett-Koehler Publishers, Inc., 2018)
The new edition of the bestselling employee development classic includes advice on talent retention in the gig economy, and a new chapter on creating a career development culture in your organization. Study after study confirms that career development is the single most powerful tool managers have for driving retention, engagement, productivity, and results. But most managers feel like they just don't have time for more meetings. This book offers a better way: frequent, short conversations with employees about their career goals that can be integrated seamlessly into the normal course of business. Beverly Kaye and Julie Winkle Giulioni identify three broad types of conversations that will increase employees' awareness of their strengths, weaknesses, and interests; point out where their organization and their industry are headed; and help them pull all of that together to design their personalized career plans. And the new chapter includes an assessment so you can measure how well your current culture supports employee development--and how to improve it.